An Investigation of Teaching Approaches in a Non-formal Setting: An Exploratory Case Study of Irish CoderDojos - Alsheaibi, Abeer Sulaiman (Trinity College Dublin. School of Computer Science & Statistics. Discipline of Computer Science, 2023)
In a world where digital technologies are playing an ever-increasing role in peoples’ professional and personal lives, it is essential that individuals acquire the computer literacy skills needed to achieve their full potential. The development of young peoples’ computer literacy has been the focus of many government, industry, and volunteer-led initiatives around the world. One such initiative is the CoderDojo movement. CoderDojo is a non-formal international network of volunteer-led, free, independent, community- based computer programming clubs for young people that was established in Ireland in 2011. Dojos are organised and run by volunteer mentors who are commonly computing professionals, university computing students, or previous participants. Significantly, however, they are not necessarily trained educators. Given the global popularity and impact of CoderDojos and initiatives like it, educators are curious to know which teaching approaches adopted play in their success. So far, there have been few studies of the teaching approaches used in CoderDojos. This thesis explores the teaching approaches mentors choose to implement while teaching programming within the context of CoderDojo in Ireland, as well as the relationship between these approaches and the CoderDojo ethos and the expectations of the CoderDojo Foundation. This research utilises Vygotsky’s social constructivism as a paradigm in order to answer the stated research questions, which focus on the views, insights, and experiences of 19 mentors. An exploratory case study design was adopted to allow for deeper insight into this particular context. Data collection included in-depth semi-structured interviews, observations of Dojos, and CoderDojos documents. Data analysis was carried out on multiple levels using thematic analysis to identify emergent themes. The findings of this thesis validate that CoderDojo offers a learning framework scaffold that is rooted in social constructivism. The non-traditional learning environments offered by CoderDojos are learner-centered as they are project-oriented and provide hands-on practical experience in a social and fun environment. The Dojo environment appears to move away from the traditional student/teacher relationship as well as the usual boundaries that exist in traditional classrooms. The traditional role of the teacher is replaced by computing-related professionals or computing-related graduate students who support and guide learners without a fixed structure and without facilitating a classroom hierarchy. This study provides insights into the teaching approaches used within the context of CoderDojo and also sheds light on some of the issues that might obstruct learning. With the Irish National Council for Curriculum and Assessment (NCCA) currently working on reviewing and redeveloping the curriculum to make computer literacy an essential part of the Irish education system, this thesis could provide educationalists and curriculum makers with insight and understanding into how young people at CoderDojos are learning computing, and may help them assess which strategies and approaches might transfer to traditional educational classrooms.
APPROVED
Keywords: non-formal learning; informal learning; coding clubs; teaching practices